Akademi Lalare Orchestra Sebagai Pengembang Kreativitas Musik Pada Anak Di Kabupaten Banyuwangi - Budy, Gandhes Sembodro (Universitas Negeri Surabaya, 2021)
Abstract: Creativity is a talent possessed by every individual and can be honed or nurtured through the right educational institutions. In a creativity formation, children need help to build their creativity. Supporting factors and the formation of creativity in children, namely with the full support of the people or the environment around them. The Lalare Orchestra Academy is an educational institution that teaches children to be more creative in playing musical instruments. This research uses descriptive qualitative method with data collection using observation and interview techniques, while the analysis technique uses the stages of reduction, presentation, and drawing conclusions. The research objective was to describe the background of the Lalare Academy Institute for orchestra and the process of developing musical creativity in children. The results showed that the background for the establishment of the Lalare Orchestra Academy was driven by the interest of the chairman of the Blambangan Arts Council, namely Syamsudin and Kadafi Kadiso as art enthusiasts to provide space and opportunities for academic music education to children. In its performances, the Lalare Orchestra Academy always presents Banyuwangi traditional music games with a number of musical instruments that are not only one device, but use many traditional musical instruments so that they are called orchestra music games. In its development, the Lalare Orchestra Academy is in great demand by children because children are given the opportunity to develop game techniques, thus motivating children to be creative. The process of developing creativity is carried out by teaching Banyuwangi traditional music playing techniques, improvisation, and its application when playing music in an orchestra. Thus children will be able to improvise existing songs and be able to play music well.Keywords: Lalare Orchestra Academy, CreativityÂ